Negotiating with the PNG Mining Industry for Women's Access to Resources and Voice : The Ok Tedi Mine Life Extension Negotiations for Mine Benefit Packages - Popoitai, Yasap; Ofosu-Amaah, Waafas (World Bank, Washington, DC, 2014)
In mining communities, women in particular often bear the negative consequences associated with mismanagement of extractive industries. Women need to be part of the processes and strategies aimed at transforming the negative aspects of the extractive industries into visible social and economic benefits in affected communities. With the permission of senior management of the Ok Tedi mining company, a World Bank consultant was included in the final 5-week long mine life extension (MLE) negotiations as an observer. The purpose was to observe women's roles in the negotiations and, through interviews with the participants, document the women negotiators' aspirations and expectations from the process. The ultimate goal is to provide a forward-looking assessment of the outcomes and draw lessons for analysis and program design not only in the Community Mine Continuation Agreement (CMCA) regions but elsewhere in Papua New Guinea (PNG) resource areas. This report documents the unique and pioneering experience in PNG of women and their roles in negotiating mining operations' benefit streams for local communities. The lessons it draws for development policy-making, planning, and program implementations are relevant both for PNG and for other countries in their attempts to make policy decisions about translating mineral wealth into inclusive and sustainable development for local communities.